(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this paper is to edit a new Iberian lead inscription found in Tos Pelat (Moncada, Valencia). In spite of his fragmentary condition, its text is possibly signary with a sacred or votive function.